EVALUASI KEGIATAN BELAJAR DAN MENGAJAR BAHASA INGGRIS MARITIM MENGGUNAKAN NEED ANALYSIS APPROACH - Endah Fauziningrum; Ever Nicolas (UNIMAR AMNI Semarang, 2019)
The cadets need to master Maritime English skills to communicate between ship and shore, between crew members, between crew and captain, between crew and passangers. So, the cadets’ efficiency in English is highly expected. Therefore, the purpose of this research are to find out the the needs of maritime cadets in English for Specific Purposes class and problem/s faced by Nautical cadets in Maritime English class. Population sampling for this research is Nautical cadets of STIMART